In vivo characterization of Linc-p21 reveals functional cis-regulatory DNA elements - Groff, Abigail F (Cell Rep, 2016)
The Linc-p21 locus, encoding a long non-coding RNA, plays an important role in p53 signalling, cell cycle regulation, and tumour suppression. However, despite extensive study, confusion exists regarding its mechanism of action: is activity driven by the transcript acting in trans, in cis, or by an underlying functional enhancer? Here, using a knockout mouse model and a massively parallel enhancer assay, we delineate the functional elements at this locus. We observe that even in tissues with no detectable Linc-p21 transcript, deletion of the locus significantly affects local gene expression, including of the cell cycle regulator Cdkn1a. To characterize this RNA-independent regulatory effect, we systematically interrogated the underlying DNA sequence for enhancer activity at nucleotide resolution, and confirmed the existence of multiple enhancer elements. Together, these data suggest that, in vivo, the cis-regulatory effects mediated by Linc-p21, in the presence or absence of transcription, are due to DNA enhancer elements.